2005
DOI: 10.1002/bies.20203
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of the apical junctional complex: mechanisms and possible roles in regulation of epithelial barriers

Abstract: Tight junctions (TJ) and adherens junctions (AJ) regulate cell-cell adhesion and barrier function of simple polarized epithelia. These junctions are positioned in the apical end of the lateral plasma membrane and form the so-called apical junctional complex (AJC). Although initially seen as purely structural features, the AJC is now known to play important roles in cell differentiation and proliferation. The AJC is a highly dynamic entity, undergoing rapid remodeling during normal epithelial morphogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 93 publications
(175 reference statements)
4
125
0
1
Order By: Relevance
“…Previous results suggested that exposure to inflammatory cytokines such as TNF, increases paracellular permeability and induces TJ protein redistribution. 6,9,42,43 Changes in TJ protein localization were assessed by immunofluorescent staining of SB tissue from wild-type and TG mice before and after T cell activation. Occludin was dramatically rearranged from the extracellular membrane to the cytoplasm in wild-type, but not in TG epithelial cells after T cell stimulation ( Figure 4A).…”
Section: Effect Of Epithelial Nf-b Activation On the Redistribution Omentioning
confidence: 99%
“…Previous results suggested that exposure to inflammatory cytokines such as TNF, increases paracellular permeability and induces TJ protein redistribution. 6,9,42,43 Changes in TJ protein localization were assessed by immunofluorescent staining of SB tissue from wild-type and TG mice before and after T cell activation. Occludin was dramatically rearranged from the extracellular membrane to the cytoplasm in wild-type, but not in TG epithelial cells after T cell stimulation ( Figure 4A).…”
Section: Effect Of Epithelial Nf-b Activation On the Redistribution Omentioning
confidence: 99%
“…Internalization of junction proteins is one mechanism for temporary or permanent modulation of cell-cell adhesion (reviewed in Bryant and Stow, 2004;D'Souza-Schorey, 2005;Ivanov et al, 2005). A number of cell-cell junction proteins have been demonstrated to internalize in response to various physiological stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] This mechanism also provides the efficient means for restructuring junctional complexes at the TJ-barrier by perturbing its permeability without requiring de novo protein synthesis. 18 For instance, it is suggested that intercellular movement is achieved by coendocytosis of apposing TJ-integral membrane proteins into the adjacent cells in a study using mouse Eph4 cells in vitro. 19 Besides, there is growing evidence that the "leaky" intestinal epithelia in chronic disorders is mediated by abnormal internalization of TJ-integral membrane proteins via endocytosis.…”
Section: The Concept Of Endocytosis In Btb Dynamicsmentioning
confidence: 99%
“…This apparently is in contrast to other blood-tissue barriers (e.g., blood-brain and blood-retina barriers), even though they are suggested to be dynamic in nature. 18 Unlike the BTB, these blood-tissue barriers do not undergo such drastic restructuring to facilitate the migration of preleptotene spermatocytes which are 10-15 μm in diameter. Besides, except for stage VIII of the epithelial cycle, the BTB remains closed to limit the entry of preleptotene spermatocytes into the adluminal compartment.…”
Section: Es and Aj)mentioning
confidence: 99%